Obesity, depression and hip pain - Schwarze, Martin; Beckmann, Nicholas A.; Schiltenwolf, Marcus (Musculoskeletal care, 2019)
Introduction Up to 64% of the general population reports experiencing chronic pain, with the hip being one of the most frequent sites. An association has been shown between chronic back pain, obesity and depression. To date, a similar association has not been investigated with chronic hip pain. Methods A total of 2,515 subjects were chosen as a representative cross-section of the German population. Each was provided with a questionnaire that included the Regional Pain Scale, European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), Beck Depression Inventory-Primary Care and Winkler social class index. Participant height and weight values were obtained from self-reports. Using logistic regression methodology, we analysed the association between hip pain, obesity and increased depression scores. Results A total of 124 (4.9%) subjects reported chronic hip pain and an additional 39 (1.5%) reported chronic hip pain that was disabling. Hip pain affected 1-5 sites (oligolocular) in 47% of cases, and was widespread (6-19 sites) in 50%. Obesity and increased values on the depression scale were associated with an increased likelihood of chronic hip pain (odds ratio [OR] 2.55 and 8.53, respectively) compared with subjects without pain. Increased values on the depression scale (OR 28.22) increased the likelihood of experiencing disabling chronic hip pain in comparison with pain free individuals. Conclusions Hip pain is rarely the sole site of pain. Obesity and increased values on the depression scale are associated with chronic hip pain. Increased values on the depression scale are associated with disabling chronic hip pain.
Gesehen am 14.04.2020